The Influence of Coping Strategy on Work Stress The Role of Moderation and Emotional Resilience On Sandeq Seafood Restaurant Workers - Andreas Junaedi Abdulah; Andi Risfan Rizaldi; A Nur Achsanuddin UA (LP2M IAIN Palopo, 2026)
Work stress among restaurant employees significantly affects productivity and psychological well-being yet is frequently overlooked. This study examines the effect of coping strategy on work stress and the moderating role of emotional resilience, grounded in the Job Demands-Resources (JD-R) Model and the Transactional Model of Stress and Coping (Lazarus & Folkman, 1984). A quantitative causal-associative approach was applied to 87 employees of Sandeq Seafood Restaurant, Makassar, selected from 110 permanent staff via the Slovin formula. Data were collected through a Likert-scale questionnaire and analysed using Moderated Regression Analysis (MRA) with SPSS 26. Results indicate that coping strategy has a significant negative effect on work stress (β = -0.705; p = 0.000), and emotional resilience significantly moderates this relationship (β interaction = -0.038; p = 0.000), strengthening the stress-reducing effect of coping strategy. The final model explains 54.1% of the variance in work stress (R² = 0.541). These findings suggest that restaurant management should design training programmes that simultaneously enhance employees' coping abilities and emotional resilience.